E-commerce managers' perceptions of pricing strategies - Hoang, Thu (2022)
This thesis strives to examine e-commerce managers' perspectives regarding their pricing strategies to gain a better understanding of their motivations and challenges during the price-setting journey. With this purpose in mind, the three research questions are formed to examine factors that influence the e-commerce owners' price-setting decisions, challenges, pricing tactics, and their justifications for implementing those decisions. The thesis aims to explore the motivations of e-commerce managers, besides obvious economic motivations, to illuminate how e-commerce managers choose their pricing strategies. In other words, the objective of this study is to understand a manager's decision-making process when they set prices for their products. With this piece of information, we can then proceed to find out the factors that influence managers' pricing strategy choices. To serve this motive, the author adopts an interpretivism approach and exploratory qualitative as the research method. After conducting the study, we found that factors that are related to humans, such as personal perspectives and judgments, are often more complicated and difficult to measure when compared to economic factors. Besides, e-commerce owners tend to struggle while deciding on a suitable pricing strategy. One of the reasons is because some of their products' value is intangible and, therefore, it was difficult for businesses to accurately put a number on it. Additionally, pricing tactics under the discount and promotion pricing category was utilized the most by e-commerce owners; however, they were not the only one. In all cases, pricing managers normally use a combination of pricing tactics. Their justifications for choosing which pricing approaches to use mainly were based on others, such as their competitors and/or other companies. In conclusion, determining the price of a product is a challenging but essential issue; therefore, the pricing strategy must be developed based on studies of different influencing factors. A single pricing strategy is never suitable for all types of retail business - every entrepreneur will need to invest time and resources to decide what works best for their product, marketing strategy, and target audience. Finally, a strategic pricing strategy does not only need to be profitable; it also needs to be sustainable over a long period of time.